Mitigation and beyond: Multiple co-benefits of solar irrigation in Bangladesh - Mitra, Archisman; Buisson, Marie-Charlotte; Osmani, Zahid; Habib, Ahasan; Hossain, Mofazzal; Siddiqui, Md. Belal; Mukherji, Aditi (International Water Management Institute, 2022)
Irrigation in Bangladesh depends primarily on imported diesel. The Government of Bangladesh (GoB) has started investing in solar irrigation pumps (SIPs) to replace diesel pumps in off-grid areas. The objective is to achieve energy security and reduce agriculture's greenhouse gas (GHG) emissions. Results from a representative survey of farmers in the command areas of the SIPs installed by the Infrastructure Development Company Limited (IDCOL) show that beyond effectively achieving the primary objective of reducing the use of diesel (mitigation), these pumps also provide other significant benefits to the farmers. The study found that these SIPs reduce farmers' cost of irrigation by 20% to 30% compared to diesel irrigation pumps, offer them access to less labor-intensive, time-saving irrigation services, and support their needs for supplementary irrigation in case of delayed monsoons.